A highly efficient thermo-optic microring modulator assisted by graphene. Issue 47 (18th November 2015) - Gan, Sheng; Cheng, Chuantong; Zhan, Yaohui; Huang, Beiju; Gan, Xuetao; Li, Shaojuan; Lin, Shenghuang; Li, Xiaofeng; Zhao, Jianlin; Chen, Hongda; Bao, Qiaoliang
Abstract : A simple method to fabricate thermo-optic modulators with high performance in a small footprint. Abstract : Graphene's remarkable electrical and optical properties afford great potential for constructing various optoelectronic devices, including modulators, photodetectors and pulse lasers. In particular, graphene-based optical modulators were demonstrated to be featured with a broadband response, small footprint, ultrafast speed and CMOS-compatibility, which may provide an alternative architecture for light-modulation in integrated photonic circuits. While on-chip graphene modulators have been studied in various structures, most of them are based on a capacitance-like configuration subjected to complicated fabrication processes and providing a low yield of working devices. Here, we experimentally demonstrate a new type of graphene modulator by employing graphene's electrical and thermal properties, which can be achieved with a simple fabrication flow. On a graphene-coated microring resonator with a small active area of 10 μm 2, we have obtained an effective optical modulation via thermal energy electrically generated in a graphene layer. The resonant wavelength of the ring resonator shifts by 2.9 nm under an electrical power of 28 mW, which enables a large modulation depth of 7 dB and a broad operating wavelength range of 6.2 nm with 3 dB modulation. Due to the extremely high electrical and thermal conductivity in graphene, the graphene thermo-optical modulator operates at a very fast switching rate compared with the conventional silicon thermo-optic modulator, i.e. 10%–90% rise (90%–10% fall) time of 750 ns (800 ns). The results promise a novel architecture for massive on-chip modulation of optical interconnects compatible with CMOS technology.